Ergonomical Assessment of Pedal Paddy Threshers with Farm Women - Mohanty, S K; Behera, B K; Satapathy, G C (Journal of Agricultural Engineering, 2009)
A commercially available pedal paddy thresher was modified and ergonomically evaluated along with the existing thresher. The study revealed that the physiological responses reduced significantly in modified pedal thresher from that of the existing pedal thresher. The HRwork, ?HR, OCR and relative cost of workload (% of VO2max), ERR in the modified thresher reduced from 135.9 to 119.4 beat/min, 65.7 to 42.6 beat/min, 0.91 to 0.72 l/min, 53.3 to 42.4 %, 18.9 to 15.0 kJ/min, respectively from that of the existing thresher. The ?HR (42.6 beat/min) was marginally higher than the limit of continuous performance (LCP) of 40 beat/min. The overall body parts discomfort reduced by 12.7 per cent. The pedal force in modified thresher decreased from 233.3 N to 188.5 N and the pedal strokes increased from 75 to 88 /min, which increased the threshing capacity of the thresher from 26.9 to 36.3 kg/h. The mean body parts discomfort score in case of modified thresher was 5.59 compared to 6.67 for the existing thresher. The increase in HR per kg of grain threshed was 55.63% less in modified thresher than that in the existing thresher. The work intensity of the thresher could be termed as moderate, whereas it was under heavy category for the existing thresher. The modified thresher was found ergonomically better and women-friendly than the existing thresher.